Asymmetrical Uptakes in 99m Tc MDP Bone Scan in Upper Extremity in Patient with Prostate Cancer: an Interesting Case - Mutsuddy, Pupree; Begum, Shamim MF; Perveen, Rahima; Salekin, Mohammad Simoon (Bangladesh Journal of Nuclear Medicine, 2018)
Asymmetrical uptake of 99m Tc MDP (methylene diphosphonate) in skeletal scintigraphy in extremity may lead to confusion in the diagnosis of metastasis or complex regional pain syndrome. After the exclusion of possible contamination in this report a case was presented with asymmetrical uptake of MDP in the upper extremity from accidental intra-arterial injection. Bangladesh J. Nuclear Med. 19(2): 152-154, July 2016